New mutation in the SOD1 (copper/zinc superoxide dismutase-1) gene in a Chinese amyotrophic lateral sclerosis (ALS) patient. Issue 7 (December 2013) - Cui, Fang; Cai, Wanshi; Wang, Zhanjun; Ren, Yuting; Li, Mao; Sun, Zhongsheng; Huang, Xusheng
Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease. More than 160 mutations of the copper/ zinc superoxide dismutase-1 (SOD1 ) gene have been identified in ALS patients. In this study, a novel SOD1 mutation was identified in a female Chinese patient with ALS. A genetic analysis identified a heterozygous mutation in exon 5 of the SOD1 gene (c.404G> C), resulting in an amino acid substitution from serine to threonine at position 134 (p.S134T). The patient's other family members (including her deceased parents) do not have any symptoms of ALS and only her son carries the same point mutation.